199k views
2 votes
What is the inverse of the following function?
y= 2^x + 3

User Polv
by
6.2k points

1 Answer

4 votes

Answer:
y=log_2(x-3)

Explanation:

To obtain the inverse of the function
y= 2^x + 3, you need to solve the equation for the variable "x":


y= 2^x + 3\\\\y-3=2^x\\\\log_2(y-3)=log_2(2^x)\\\\x=log_2(y-3)

Now you need to exchange the variable "x" with the variable "y". Then:


y=log_2(x-3)

Finally, you get that the inverse of the function
y= 2^x + 3 is:


y=log_2(x-3)

User Corneil Du Plessis
by
6.0k points